THE INFLUENCE OF LEADERSHIP, ORGANIZATIONAL CAPACITY DEVELOPMENT COMMITMENT, INFORMATION AND COMMUNICATION TECHNOLOGY ON IMPROVING EMPLOYEE PERFORMANCE SUPPORTING SYSTEMS AND PROFESSIONAL HUMAN RESOURCE COMPETENCY DEVELOPMENT THROUGH THE HUMAN CAPITAL DEV - Kukuh Zaldhy; Budi Supriyatno (Faculty of Social and Political Science Universitas Galuh, 2023)
Influence of improving the support system and developing the competence of professional human resources through the provision of the Human Capital Development Plan (HCDP) Roadmap at the Secretariat General of DPD RI is the extent to which leadership, organizational capabilities, information and communication technology support employee performance systems and affect performance employees and professional human resource competencies, in devoting skills, knowledge, skills, energy and time where work motivation expects rewards from companies that can satisfy their need. The purpose of this study was to identify and analyze the effect of Work Leadership, organizational capabilities, information and communication technology supporting employee performance systems and influencing employee performance and professional human resource competence in the provision of HCDP at the Secretariat General of DPD RI. The analysis tool in this study uses a quantitative analysis approach, which is an approach to test a hypothesis by using accurate statistical data tests. In this study, independent testing was carried out (X1 = leadership, X2 = commitment to organizational capacity building, X3 = information and communication technology) on the dependent variable (Y1 = employee performance supporting system. Y2 = professional human resource competency development). Testing the hypothesis can be stated as follows Ha: influence on leadership, organizational commitment, information and communication technology, employee performance and professional human resource development competencies at the Secretariat General of DPD RI, Ho: leadership. commitment, information and communication technology, employee performance supporting systems and professional human resource development competencies have no effect on the provision of HCDP at the DPD RI Secretariat General, if: T count < T table then ho is accepted, the independent variable (motivation) has no effect on the dependent variable (employee dependent variable (employee performance). T count > T table then accepted ho, the independent variable (motivation) has an effect). The results of the study through quantitative analysis tests to test the hypothesis of accurate statistical data are that the variables X1 and X2 leadership, commitment, information and communication technology have a positive effect on employee performance and human resource competence. The hypothesis put forward in this study is that leadership, commitment and information and communication technology, and employee competence influence the provision of HCDP in improving performance at the Secretariat General of DPD RI.